Student Movements and the Power of Disruption - Gabriela Gonzalez Vaillant (Coordinamento SIBA, 2019)
We seek to clarify the nature of militant student protest by proposing a theoretical distinction between two types of student-movement-initiated disruption that are too-often viewed as similar: structural disruption within educational institutions, centered around students' refusal to perform their role as such; and invasive disruption of other institutions, in whose functioning students do not have a routinized role. By drawing on a newspaper-based database of student-initiated protest in Argentina, triangulated by analysis of secondary accounts of these events and in-depth interviews with the activists who planned and implemented the protest, we seek to understand the strategic logic that leads to disruptive protest and to explore the differing dynamics that characterize structural and invasive disruption. Both structural and invasive protest by students (and other organized social groupings) can successfully interfere with the normal functioning of society and can therefore create usable leverage against institutional power holders. However, the tactical choice and the outcome of such confrontations derives from a complex equation of situational variables. The variables specific to student protest include the institutional target designated for disruption, whether the target has the formal authority and/or resources to grant the demanded reform, whether non-students who work or otherwise participate in the targeted structure support or oppose the demands and tactics of the students, and whether the protesting students have active allies among various non-student stakeholders. We conclude that structural disruption on campus can be a surer and less difficult-to-implement strategy, that it can generate leverage without the creation of alliances with outside groups and can force concessions if the administration has the authority and resources to deliver meaningful reform. In many circumstances, however, the institutional educational leadership cannot deliver meaningful concessions, and stu-dents therefore consider invasive disruption of neighboring structures aimed at delivering more comprehensive reforms, and consequently face far more complicated strategic and tactical decisions if they wish to generate productive leverage. These strategic and tactical choices rely on congealed experience from current and prior student protest and their capacity to generate alliances mediated by their understanding of what can succeed.